Empacotamento de filtro de dessalinização do semiárido pernambucano para avaliação da Moringa oleífera lam. como biossorvente. - Gomes Filho, Armando José (2019)
In northeastern Brazil, coping with the scarcity of quality water is being carried out through the desalination of brackish waters, aiming to enable conditions of more noble uses. The desalination of brackish water occurs through the Desalinizer by the reverse osmosis process, which produces fresh water and a highly concentrated reject in salts. In this sense, studies were carried out by dimensioning, constructing and evaluating the prototype of fixed bed columns with Moringa oleifera Lam. As adsorbent and fluid dynamics in the removal of salts present in the withdrawal from the Semiarid desalinators Pernambuco. For this, Moringa seeds were collected and prepared according to the treatments: no seed (control), whole seed with and without bark, crushed seed with and without bark, ground seed with and without bark, with five replications. The doses were equivalent to 2.0 g of the Moringa seed to 200 ML of reject, with contact time corresponding to 30, 60, 120 and 180 minutes, in a completely randomized statistical design, under laboratory conditions, with a total of 140 units Experimental. At the end of the experiment, the physicochemical and statistical analyses were performed by analysis of variance (ANOVA), using the F test, with a confidence interval of 95%. It was observed from the laboratory tests performed that the seeds with bark, ground or crushed, have significant potential in the treatment of the reject. In 30 minutes of contact with the reject the sodium reduction was 98%, the hardness (calcium and magnesium) and the chloride of 4% enough to change the physicochemical properties, making it suitable for consumption. In the second stage, the filter was packaged with Moringa oleifera with crushed bark whose extract was collected every 5 minutes up to 60 minutes. After the physicochemical analysis, the statistical data showed that 5 minutes of contact was sufficient for the removal of sodium, calcium, magnesium and chloride, allowing the reject a possible applicability in agriculture.